KAJIAN TANAH ENDAPAN PERAIRAN SEBAGAI MEDIA TANAM PERTANIAN KOTA - Haryanta, Dwi; Thohiron, Moch.; Gunawan, Bambang (2477 - 6165, 2017)
Siltation of the river, ditches, reservoirs in urban areas is a problem because it causes flooding. The government annually undertakes dredging of the precipitate for the flow of water to flow smoothly. Soil sedimentary water potential to be utilized as a medium of planting in the development of urban agriculture. The research was conducted by survey method in water area of Surabaya. The sample was taken using random method of choosing, that is choosing condition of place environment and soil condition which is possible for planting medium. Soil sediment samples were observed for pH, color,structure, texture, organic matter content, Nitrogen (N-total), K2O and P2O5. The result of research showed that all of the textured sedimentary soil content of clay was about 89,87-92,14%, organic material was about 5,96-7,60%, total N was about 0,09-0,13%, K2O was about 0,88-1,12%, and P2O5 was about 2,08-2,44%. The color of soil was grayish-black. The mud deposits of the housing sewer were the most crumbling and the most consumptive reservoir was sludge. Sewage soil sludge is potentially used as a planting medium in the development of urban agriculture. Keywords: Planting Media, Urban Agriculture, Soil Sedimentary.